Heavy Metal Distribution in Aquatic Products from Eastern Guangdong and Associated Health Risk Assessment - Jinyan Liu; You’an Yu; Zewei Sun; Keqin Zhang; Ping Li; Wenhua Liu; Ran Bi (Toxics)
With the rapid industrialization and urbanization of coastal areas, marine pollution (such as heavy metals) is increasingly contaminating the environment, posing significant public health risks. Eastern Guangdong, a key aquaculture and fisheries hub in China, has a growing market for aquatic products. Heavy metals persist in the environment and are difficult to degrade and bioaccumulate in marine organisms through the food web, presenting carcinogenic and mutagenic risks to humans, as top predators. This study analyzed 10 key species commonly consumed by residents of eastern Guangdong (bivalves, crustaceans, and fish), measuring the concentrations of six heavy metals (As, Cd, Cr, Cu, Ni, Pb) using inductively coupled plasma mass spectrometry (ICP-MS). Pollution levels were assessed using the pollution index (Pi), and dietary exposure risks were evaluated via the target hazard quotient (THQ) for different age groups. Results showed that Pi values for all metals were within normal background levels, but bivalves had a high capacity for Cd accumulation, with pollution severity ranking as bivalves > crustaceans > fish. The THQ values for both adults and teenagers were <1 across all samples, indicating no risk to the health of residents. However, the TTHQ for Sanguinolaria sp. exceeded 1, indicating potential health risks. This study highlights the health risks of consuming heavy metal-contaminated aquatic products, particularly bivalves. Reducing the consumption of these high-metal species could help lower dietary exposure and associated risks. Our findings provide essential data for the quality assessment of aquatic products and offer dietary recommendations for residents in eastern Guangdong.